Minimally invasive esophagectomy for caustic ingestion after 73 years and over 200 endoscopic dilations: is it just a matter of time? - Marchesi, Federico; Rapacchi, Chiara; Pattonieri, Vittoria; Tartamella, Francesco; Mita, Maria Teresa; Cecchini, Stefano (Acta Biomedica Atenei Parmensis, 2016)
Refractory esophageal strictures are a common sequela of caustic ingestion. If endoscopic dilation becomes ineffective, esophagectomy represents the only therapeutic option. The minimally invasive approach, specifically the thoracoscopic access in prone position, may allow postoperative morbidity to be reduced. We present the first case described in the Literature of minimally invasive esophagectomy in prone position for a long-term failure of endoscopic dilation after caustic ingestion.